Correspondences and Fractures: Lesbians Talk Queer Formations - Laura Guy; Cherry Smyth (British Art Studies)
This interview between the poet Cherry Smyth and the writer Laura Guy focuses on Smyth's contribution to feminist and queer activism and cultural production after she arrived in London from Ireland in the early 1980s. The conversation covers a range of activities in which Smyth was involved in the ensuing years, including the Greenham Common Women's Peace Camp and the Troops Out Movement; feminist and community film and video production; Irish women's writing and her contribution as a cultural critic to the formation of new queer perspectives and politics in the early 1990s, particularly in her books *Lesbians Talk: Queer Notions* (1992) and *Damn Fine Art: By New Lesbian Artists* (1996). In the correspondences and fractures signalled by these connected yet heterogeneous practices, the category of "queer" emerges as a site of potentiality not only in the recent past but also for a younger generation of artists working in Ireland today.